Host-cell interactions in HBV infection and pathogenesis: the emerging role of m6A modification. Issue 1 (1st January 2021) - Kostyusheva, Anastasiya; Brezgin, Sergey; Glebe, Dieter; Kostyushev, Dmitry; Chulanov, Vladimir
ABSTRACT: Hepatitis B virus (HBV) is a DNA virus with a complex life cycle that includes a reverse transcription step. HBV is poorly sensed by the immune system and frequently establishes persistent infection that can cause chronic infection, the leading cause of liver cancer and cirrhosis worldwide. Recent mounting evidence has indicated the growing importance of RNA methylation (m6A modification) in viral replication, immune escape, and carcinogenesis. The value of m6A RNA modification for the prediction and clinical management of chronic HBV infection remains to be assessed. However, a number of studies indicate the important role of m6A-marked transcripts and factors of m6A machinery in managing HBV-related pathologies. In this review, we discuss the fundamental and potential clinical impact of m6A modifications on HBV infection and pathogenesis, as well as highlight the important molecular techniques and tools that can be used for studying RNA m6A methylome.